Effect of phosphorus addition on the sintering and dielectric properties of Pb(Zr0.52Ti0.48)O3 - Saha A.K.; Kumar D.; Parkash O.; Sen A.; Maiti H.S. (My University, 2025)
It has been found that the sintering temperature of piezoelectric Pb(Zr0.52Ti0.48)O3 (PZT) can be reduced by phosphorus addition without compromising the dielectric properties. A sintered density of 98.6% of the theoretical density was obtained for 2wt.% P2O5 addition after sintering at 1050°C for 4h. The P2O5 addition, either above or below 2wt.%, showed an inferior densification. Coincidentally, the P2O5 addition gave rise to a lower lead loss, and the dielectric constant showed a peak at 1wt.% P2O5 addition. © 2003 Elsevier Science Ltd. All rights reserved.